Embracing Floating Architecture and Green Infrastructure: Coastal Innovation for Resilient Waterfront Communities in Batam City. - Novya Mardhika; Imanda Utami Rangkuty, Gladies; Dinar Agupriyanti, Carissa (Program Sarjana Arsitektur Universitas Internasional Batam, 2025)
In response to the pressing issues of environmental degradation due to uncontrolled urbanization, leading to alarming greenhouse gas emissions as well as the consequential rise in sea levels that is caused by the extensive loss of ice, this article explores the solution to coastal areas that are prone to flood which require a re-evaluation to accommodate growing populations. The article proposes floating architecture as the solution to this issue. Floating architecture seamlessly unites with the water bodies. This paradigm shift aims to tackle limited land availability, urbanization pressure, and rising sea levels by adapting to water levels. Floating architecture allows the ability for cities to expand to the waters when the land is scarce. Floating architecture also serves as attractions creating unique experiences and enhancing the communities surrounding. This study uses qualitative methodology followed by a descriptive approach to analyze completed and prospective projects to obtain insight into floating structure and design considerations. Results show that integrating sustainable design with floating architecture is much more cost-effective, sustainable, efficient, mobility, and flexible than land reclamation.